Eksplorasi Populasi dan Kepadatan Genus Nematoda Parasit pada Rizosfir Tanaman Kopi di Kota Solok, Sumatera Barat: Exploration of Population and Density of Parasitic Nematode Genus in Coffee Plant Rhizom in Solok City, West Sumatra - Duma Putri Tama; Winarto; Trizelia (Jurusan Budidaya Perkebunan, 2024)
Coffee is a plantation crop that has high economic value among other plantation crops and plays an important role as a source of foreign exchange for the country. The decline and low productivity of coffee plants in coffee production centers in Solok City, West Sumatra is one of the causes of plant parasitic nematode attacks. This nematode attack causes disrupted plant growth and reduces the value of crop production both in quantity and quality. This study aims to determine the diversity and population density of parasitic nematodes in the rhizosphere of coffee plants in Solok City, West Sumatra. This research was conducted from March to July 2023 at the Laboratory of Biological Control, Department of Plant Protection, Faculty of Agriculture, Andalas University. Soil samples were taken in two central areas of coffee plantations in Solok City, West Sumatra. In the rhizosphere of coffee plants in Solok City, four genera of parasitic nematodes were found, namely: the genera Pratylenchus, Helicotylenchus, Meloidogyne, Rotylenchulus, Paratylenchus, and Tylenchorhynchus. The highest frequency of presence of nematodes, namely the genus Rotylenchulus, was 50.99 belonging to the medium category in Jorong Kayu Aro, and 44.80 in the rare category in Jorong Kayu Jao.